Pengaruh Free Cash Flow dan Struktur Aset Terhadap Kebijakan Hutang Dengan Pemoderasi Risiko Bisnis - nur ainiyah; Tatas Ridho Nugroho (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2020)
Agency conflicts can be reduced by monitoring to align the interests of related parties. The existence of this supervision will lead to agency costs. To reduce agency costs, it can be done by increasing assets through debt. Business risk can be used as a foothold in making decisions regarding debt policies for companies. Business risk is influenced by the uncertainty of revenue acquisition for the company. Companies that have a business with business risk are more likely to reduce the amount of debt, because the company does not want to increase the risk of debt repayment difficulties. The greater the risk implies in the small debt for the company. This is certainly influenced by the company's ability to repay debt due to uncertainty (volatility) of income or profits that can be achieved by the company. The sample used was 70. The results of the study concluded that business risk variables could simultaneously be a moderating effect of free cash flow and asset structure on debt policy. this can be seen from an increase in influence of 0.013 or 1.3%. Partially business risk cannot be used as a moderating effect of free cash flow on debt policy. But business risk can be partially used as a moderating effect of asset structure on debt policy